Analysis of pork adulteration in commercial burgers targeting porcine-specific mitochondrial cytochrome B gene by TaqMan probe real-time polymerase chain reaction - Md. Eaqub, Ali; Uda, Hashim, Prof. Dr.; Thikra, S. Dhahi; Mustafa, Shuhaimi, Assoc. Prof. Madya Dr.; Yaakob, Che Man, Prof. Dato' Dr.; Md Abdul Latif, Dr. (Springer-Verlag, 2013)
Link to publisher's homepage at http://link.springer.com/